2003
DOI: 10.1191/0960327103ht347cr
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis: an obscure complication of organophosphate intoxication

Abstract: Acute pancreatitis secondary to organophosphate intoxication is a rare and generally well-course condition, but it is important to be aware of this complication for appropriate clinical management. There are a few reports about this subject in the literature, but it is believed that there are more cases than are reported for this condition. Because symptoms of toxicity can mask this severe complication, we report two cases of acute pancreatitis due to organophosphate intoxication for alerting this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Another study, however, found that exposure to malathion resulted in decreased glucose-stimulated insulin secretion accompanied with patchy degenerative changes in the islets of Langerhans (Pournourmohammadi et al, 2007). Similarly, other human and animal studies also found that organophosphorus and carbamate insecticide can cause acute pancreatitis, which potentially influence insulin secretion (Dressel et al, 1978; Gokel et al, 2002; Goodale et al, 1993; Harputluoglu et al, 2003; Hsiao et al, 1996; Kandalaft et al, 1991; Lankisch et al, 1990; Marsh et al, 1988; Moore and James, 1981; Moritz et al, 1994; Panieri et al, 1997; Weizman and Sofer, 1992). …”
Section: Mechanisms Of Insecticide-induced Change In Glucose and Lmentioning
confidence: 85%
“…Another study, however, found that exposure to malathion resulted in decreased glucose-stimulated insulin secretion accompanied with patchy degenerative changes in the islets of Langerhans (Pournourmohammadi et al, 2007). Similarly, other human and animal studies also found that organophosphorus and carbamate insecticide can cause acute pancreatitis, which potentially influence insulin secretion (Dressel et al, 1978; Gokel et al, 2002; Goodale et al, 1993; Harputluoglu et al, 2003; Hsiao et al, 1996; Kandalaft et al, 1991; Lankisch et al, 1990; Marsh et al, 1988; Moore and James, 1981; Moritz et al, 1994; Panieri et al, 1997; Weizman and Sofer, 1992). …”
Section: Mechanisms Of Insecticide-induced Change In Glucose and Lmentioning
confidence: 85%
“…Indeed, Rezg et al (2006) have suggested a time dependent variation in glucose homeostasis that was probably repeated daily in subchronic exposure until leads to diabetes induction in chronic exposure in consequence to pancreatic endocrine and exocrine function damage (pancreatitis) a well known as complication of OP poisoning (Dressel et al, 1979;Gokel et al, 2002;Harputluoglu et al, 2003;Kandalaft et al, 1991;Lankisch et al, 1990;Panieri et al, 1997).…”
Section: Effect Of Malathion Administration On Glycogen Phosphorylasementioning
confidence: 98%
“…Renal failure, 4 diabetes, and especially obesity are substantial risk factors for disease development and severity. Although an infrequent cause of pancreatitis, exposure to potent cholinergic agonists as seen with scorpion bites 5 and exposure to select insecticides6, 7 also can cause disease and may be mimicked by preparations that use supraphysiologic concentrations of toxins or neurohumoral agents to induce disease 8 . Infections with Coxsackie virus can cause acute pancreatitis in children, although the incidence is unclear; this response has been reproduced in animal models 9 .…”
mentioning
confidence: 99%